2022
DOI: 10.19074/1814-8654-2022-45-32-83
|View full text |Cite
|
Sign up to set email alerts
|

Saker Falcon in the Karatau Mountains and surrounding territories (Kazakhstan) – results of 2022 research

Abstract: Saker Falcon (Falco cherrug) is one of the most threatened falcon species of Northern Eurasia, the range and the number of which has fallen catastrophically over the last four decades. One large breeding group was concentrated in the Karatau Mountains in southern Kazakhstan. Based on the results of studies in 2010 and 2022, we modeled Saker Falcon distribution in Google Earth Engine using the image classification method – Random Forest (probability + regression). The area of Saker Falcon breeding biotopes in K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Gubin (2015; 2020) also does not provide any new information about the RNS in Ustyurt and the Aral Sea region. During the period of studies from 2003 to 2020 in the Aral-Caspian region, the RNS was not observed by ornithologists in the breeding period at all, despite the fact that several hundred nests of the Saker Falcon (Falco cherrug) were found in the region during this time (Karyakin et al, 2004;2005a;2005b;Pazhenkov, Korzhev, 2006;Mitropolsky et al, 2009;Levin, 2011a;2012;Smelansky et al, 2020). It is likely that the RNS is now only rarely seen here during the non-breeding period, as a single bird was recorded in the hills of the Kok-Aral Peninsula on September 29, 200529, (Kovalenko, 2006.…”
Section: Korelov Et Al (1986)mentioning
confidence: 95%
See 1 more Smart Citation
“…Gubin (2015; 2020) also does not provide any new information about the RNS in Ustyurt and the Aral Sea region. During the period of studies from 2003 to 2020 in the Aral-Caspian region, the RNS was not observed by ornithologists in the breeding period at all, despite the fact that several hundred nests of the Saker Falcon (Falco cherrug) were found in the region during this time (Karyakin et al, 2004;2005a;2005b;Pazhenkov, Korzhev, 2006;Mitropolsky et al, 2009;Levin, 2011a;2012;Smelansky et al, 2020). It is likely that the RNS is now only rarely seen here during the non-breeding period, as a single bird was recorded in the hills of the Kok-Aral Peninsula on September 29, 200529, (Kovalenko, 2006.…”
Section: Korelov Et Al (1986)mentioning
confidence: 95%
“…Kostin's (1956) intricate directions on the possibility of the RNS nesting on the chinks of Ustyurt were questioned by L.S. Stepanyan (1975) (Karyakin et al, 2004;Карякин и др., 2005а;2005b;Паженков, Коржев, 2006;Митропольский и др., 2009;Левин, 2011a;2012;Смелянский и др., 2020). Вероятно, здесь шахин в настоящее время встречается только крайне редко в негнездовой период, так как в in his essay on the RNS for the bird checklist of the Almaty region notes that in 2004 during 2 months of work in Ustyurt (April-May) the RNS was not encountered at all.…”
Section: Korelov Et Al (1986)mentioning
confidence: 99%
“…In 2010, 11 survey plots with a total area of 1,273.2 km 2 were laid out in the Karatau mountains, and linear routes were drawn on six chink areas with a total length of 20.85 km (Karyakin et al, 2010). In 2022, 16 survey plots with a total area of 4,191.54 km 2 , some of which partially overlapped with 2010 plots (the overlap area was 521.72 km 2 ) (Karyakin et al, 2022b).…”
Section: методика исследованийmentioning
confidence: 99%
“…At the same time, in 2022 all previously identified nesting colonies of the Griffon Vulture were examined. The total length of auto routes in 2010 was 1,895 km (Karyakin et al, 2010), in 2022 -9,655 km (including 3,393 km in April-May and 6,262 km in July) (Karyakin et al, 2022b).…”
Section: методика исследованийmentioning
confidence: 99%
See 1 more Smart Citation